Carbon and oxigen minibeam radiation therapy: A Monte Carlo dosimetry study. (September 2016) - González, W.; Peucelle, C.; Prezado, Y.
Abstract : Introduction: Minibeam radiation therapy (MBRT) is a promising RT approach born at synchrotrons that combines the use of a spatial fractionation of the dose with the utilization of submillimetric field sizes (500–700 μ m). Contrary to conventional RT, the dose profiles in MBRT consist in peaks and valleys, making the peak-to-valley-dose ratio a very important dosimetric parameter, since in order to spare the normal tissues, high PVDR and low valley doses are required. MBRT has been shown to further increase the normal tissue resistance compared to standard RT. Purpose: The aim of this work was to perform an in depth dosimetric evaluation of carbon and oxygen minibeam radiation therapy. Materials and methods: The dose distributions of rectangular minibeams of 600 μ m × 2 cm of C and O ions impinged in a water phantom with the Monte Carlo simulation code GATE v6.2 (Geant4.9.5). Results: PVDR and valley doses were assessed for different irradiation configurations. In particular, a detailed evaluation of the role of secondary particle contamination of the valley doses, which is one of the more critical aspects of MBRT, has been carried out. Conclusion: The favourable dose distributions obtained indicate that these novel RT approaches might allow reducing the side effects in normal tissues. It should also make charged particle therapy more amenable to administration in either a single dose fraction.